Nalar Maslahat Dalam Kebijakan Zonasi Dan Penguatan Pendidikan Karakter - Firman Muhammad Arif (Institut Agama Islam Negeri Palopo, 2019)
Zoning Policy and Character Education Strengthening are government policies in the education sector. Zoning policy aims at efforts to restore national education and strengthen character education aimed at developing religious values which then accelerate the strengthening of individual character so that they are able to control themselves and develop noble character in society and nationhood. Mass reasoning contained in the qawa'id fiqhiyyah and usul al-fiqh is used as an instrument to measure the weight of maslahat contained in government education policies. Zoning policies and strengthening character education are considered as media to achieve goals. The mass content contained in the zoning policy shows maximum weight than the mafsadah (something bad or potentially bad). National education arrangement that prioritizes citizenship character has triggered the government to issue a policy to strengthen character education with the maslahat (something good, potentially good) weight with consideration of the sociological, cultural and political aspects of the local government. The manifestation of strengthening character education is full day school allowing it to be applied in urban school areas and vice versa will increase the heavy burden of parents and students in various schools in rural areas so that full day school is not forced but chosen.